Construction of Dielectric Model of Nonaqueous Reactive Polyurethane Grouting Materials - Meili Meng; Zhanglan Chen (Advances in Polymer Technology, 2022)
In order to reveal the dielectric properties of the nonaqueous reactive polyurethane grouting material, combined with the electron microscope test analysis, it can be seen that the nonaqueous reactive polyurethane material is a porous two-phase body composed of a polyurethane matrix and closed cells. At the microscopic scale, the porous two-phase physical model is established, and the dielectric model of the material is constructed on this basis. In order to verify the dielectric model, 40 groups of nonaqueous reactive polyurethane specimens with different densities were designed and prepared in this paper. The dielectric permittivity was measured by a vector network analyzer (VNA) with an open coaxial probe within the frequency range of 1050 MHz~5010 MHz for the first time, and the dielectric properties and influencing factors were revealed according to the test data. The result shows that the dielectric permittivity of nonaqueous reactive polyurethane materials increases with the increase of density, and decreases slightly with the increase of frequency. Compared with the three models of the Rule of Mixture, Clausius-Mossotti Model and Lichtenecker Model, the calculation accuracy of the Maxwell-Garnett Model is higher, and the calculation results are more consistent with the experimental results of nonaqueous reactive polyurethane grouting materials. The experimental results can be applied to the nondestructive testing of polyurethane grouting materials and provide reference and basis for the quality evaluation of polymer structures.